Occult Placenta Accreta: Risk Factors, Adverse Obstetrical Outcomes, and Recurrence in Subsequent Pregnancies - Mullen, Clodagh; Battarbee, Ashley N.; Ernst, Linda M.; Peaceman, Alan M. (American Journal of Perinatology, 2019)
Objective To assess the risk factors, adverse obstetrical outcomes, and recurrence risk associated with pathologically diagnosed occult placenta accreta.Study Design This was a retrospective observational study of clinically adherent placentas requiring manual extraction that underwent pathological examination. Cases were defined as those with histological evidence of placenta accreta, and controls were defined as those without accreta. All subsequent pregnancies were evaluated to determine the recurrence risk of occult accreta in future pregnancies.Results Of 491 women with clinically adherent placentas, 100 (20.1%) with a pathological diagnosis of occult accreta were compared with 391 (79.9%) without occult accreta. In bivariable analysis, risk factors associated with occult accreta included a history of previous cesarean (19 vs. 10.7%; p = 0.03) and prior uterine surgery (35 vs. 19.7%; p = 0.001). Adverse obstetrical outcomes were more common in women with occult accreta including postpartum hemorrhage (59 vs. 31.7%; p < 0.001) and peripartum hysterectomy (21 vs. 0.3%; p < 0.001). In 130 subsequent pregnancies, there was an increased risk of retained placenta (42.9 vs. 19%; p = 0.04) and recurrence of occult accreta (29.6 vs. 6.8%; p = 0.05).Conclusion Occult accreta is associated with an increased risk of hemorrhagic morbidity and recurrence of morbidly adherent placenta in subsequent pregnancies.
Keywords: retained placenta; focal accreta; postpartum hemorrhage; placental pathology; occult accretas; histological accreta